Participation, Digital Divides and Political Polarisation: The Case of the Ministry of Health, 2019-2022 - Mejía Navarrete, Julio; Menéndez Cóndor, Pamela Fabiola (Mediaciones Sociales, 2025)
Political and civic participation has expanded in recent years in the country, a process that has been strengthened by the development of public institutions’ social media platforms during the COVID-19 pandemic. This article analyzes the Ministry of Health’s Facebook page and website during the pre-pandemic, pandemic, and post-pandemic periods. The paper is divided into four sections: first, it examines political participation and digital citizenship in relation to the Ministry of Health’s activities. Second, it examines the digital divides through access, use, and quality of technological devices in relation to digital platforms. Third, the paper analyzes the main health topics debated in digital public opinion using word clouds. Fourth, it studies the constitution of citizen political polarization around the Ministry of Health’s actions. Finally, the methodology used resorted to Big Data techniques, and additionally, interviews and surveys were also applied. In conclusion, the COVID-19 pandemic significantly contributed to the population’s digital relationships with the Ministry of Health. While it is true that political participation in the management of the Ministry of Health (MINSA) has increased, it has primarily developed through consultative political participation, which emphasizes communication and consultation on public health policies. Finally, the role of citizenship in the Ministry of Health has expanded, particularly highlighting the importance of the population’s civic rights, which revolve around the freedom of digital communication.